Hydrogeochemical Assessment of Groundwater Quality and Suitability for Drinking and Agricultural Use. The Case Study of Fars Province, Iran - Aghaei , Yasamin; Nazari-Sharabian, Mohammad; Afzalimehr, Hossein; Karakouzian, Moses (Engineering, Technology & Applied Science Research, 2023)
This study aims to evaluate the hydrogeochemistry of aquifers in Fars province, Iran, from 2007 to 2017 and assess the groundwater’s suitability for drinking and agricultural uses. A total of 35,000 samples were collected from wells and qanats across the province. Piper, Gibbs, and Durov diagrams were used to assess the hydrochemical facies and processes. Cross plots of different ions were investigated to assess ion exchange and determine the effects of anthropogenic activities, as well as the weathering and dissolution of different rocks and minerals in the aquifers. Groundwater quality and suitability for agricultural and drinking purposes were also assessed using physicochemical parameters including pH, Electrical Conductivity (EC), Total Dissolved Solids (TDS), Total Hardness (TH), and calcium, magnesium, sodium, potassium, bicarbonate, sulfate, and chloride concentrations. Suitability for domestic purposes was assessed by comparing these values with the WHO standards. Sodium and alkalinity hazards, including Sodium Adsorption Ratio (SAR), sodium percentage (Na%), Permeability Index (PI), Magnesium Hazard (MH), and Residual Sodium Carbonate (RSC) were used to assess irrigation suitability, along with plotting Wilcox and USSL diagrams.